Sosialisasi Upaya Pencegahan dan Penanggulangan Bahaya Kebakaran di Sekolah Luar Biasa (SLB) Kota Balikpapan - Siska Ayu Kartika; Agung Prabasworo; Abdy Nugroho (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
In general, the main factor of the many casualties, damage and losses arising from disasters is the lack of understanding and awareness of the community, especially regarding how to prevent and deal with fire hazards. One of the fundamental efforts to increase awareness and awareness to foster a culture of alert is to conduct socialization activities, and preparedness exercises. The implementation of special awareness raising and preparedness exercises also involves vulnerable groups, such as children, the elderly and homeless, persons with disabilities and people with special needs. So that it is deemed necessary in the implementation of community service this time to socialize efforts to prevent and combat fire hazards to all teaching staff, school officials and Special Case School in Balikpapan. The program was held for 1 day, April 26, 2019. Cooperation between the community service teams at the University of Balikpapan was very good so that efforts to increase the understanding of teachers and students regarding the efforts that could be made to prevent and overcome the danger of fire could proceed with well.